Review on Implementing Smart Water Grid for Smart Cities in India - Behera, Shishir Kumar; Pradhan, Bibhuti bhusan (International Journal of Psychosocial Rehabilitation, 2019)
This paper face an acute shortage of resources in today’s world such as Fuel, Clean Water, Shelter and Hygienic Food. And only 0.1% of the total Water on Earth is available to living beings as clean and fresh water. The human population on Earth is also increasing day by day and most sources of clean water are depleting. The level of groundwater is rapidly declining and the pollution of groundwater by chemicals [water and soil pollution] has alarming effects on human beings ’ sustainable growth. Worldwide, water scarcity is rising at the most alarming rate and millions of people around the world have no access to water. India suffers from one of their worst shortages of water. The crops get ruined, and water shortages in its underground reservoirs lead to drought and emptiness. The households waste most of the clean water and this usually happens in modern societies and recent establishments. This review paper discusses the need for water management, water scarcity control measures and the idea of a smart water grid for water conservation, as well as the challenges of implementing it in India